Ceratocystis fimbriata on Brown Salwood (Acacia Mangium) in Banyuasin, Indonesia - Amelia, Rizki Putri; Muslim, A.; Damiri, Nurhayati; Hamidson, Harman; Suwandi; Pratama, Rahmat (Journal of Scientific Agriculture, 2024)
Acacia mangium in Banyuasin commonly grows in plantations and along roadsides as a shade plant. Generally, this plant is also useful as a material for making household furniture, firewood, and paper pulp. Since 2022, numerous reports of these plants wilting and dying suddenly, have drawn significant attention in the plantations. Our study recorded that the presence of cankers on the stems, lesions on the sapwood, blackened vascular tissue, discoloration of leaves, wilting of the canopy, and massive tree mortality characterize this disease. Based on the morphological characteristics and sequencing of the ITS and β-tubulin genes, the pathogen causing canker and wilt disease in A. mangium in Banyuasin has been confirmed as Ceratocystis fimbriata. The pathogen strain exhibits strong pathogenicity on A. mangium seedlings during inoculation tests in nurseries. Host range tests showed that the isolate can also thrive on Acacia crassicarpa and jackfruit (Artocarpus heterophyllus). Therefore, it is crucial to identify appropriate management solutions to minimize damage to A. mangium plants.